Poststroke Erectile Dysfunction in Cameroon: Prevalence, Associated Factors, and Quality of Life. (3rd December 2021) - Massi, Daniel Gams; Mountap, Gervais Ngoupayou; Moby, Hervé Edouard; Ngalle, Frantz Guy Epoupa; Mouliom, Sidick; Doumbe, Jacques; Mapoure, Njankouo Yacouba
Abstract : Background . Stroke is a severe disease due to its morbidity-mortality. It is the first cause of acquired disability including erectile dysfunction (ED). The purpose of this study was to determine the prevalence of ED in stroke patients at the Douala General Hospital, to identify associated factors and to evaluate their quality of life. Materials and Methods . A cross-sectional study was conducted over a period of seven months from November 2016 to May 2017 on two groups of patients in neurology, cardiology, and endocrinology units of the Douala General Hospital (Cameroon): stroke patients (stroke+) and nonstroke patients (stroke-). We collected sociodemographic and clinical data using a preestablished questionnaire. Erectile function was assessed using International Index of Erectile Function (IIEF-5). Associated and predictive factors were determined using univariate and multivariate analyses. Results were significant for a p value < 0.05. Results . A total of 269 patients were included, among them 87 stroke+ (32.34%) and 182 stroke- (67.66%) (controlled group). The mean age was 56.37 ± 12.89 years and 57.18 ± 10.24 years of stroke+ and stroke-, respectively (p = 0.608 ). Prevalence of poststroke ED was 64.4% (OR = 3.41, 95% CI: 1.99-5.82, p < 0.001 ). The average time of occurrence of the poststroke ED was 5 ± 5.85 months. Diabetes and dyslipidemia were the predictive factors of occurrence of poststroke ED. Depression was found both in stroke+ with ED and stroke+ without ED with no difference (p = 0.131 ). Conclusion . About two-thirds of stroke patients developed ED. Diabetes and dyslipidemia were predictive factors of ED in stroke patients.